2019
DOI: 10.1007/s10798-019-09507-7
|View full text |Cite
|
Sign up to set email alerts
|

Finding the connection between research and design: the knowledge development of STEM teachers in a professional learning community

Abstract: Research and design activities are becoming more important in Science, Technology, Engineering and Mathematics (STEM) and D&T (design and technology) education. Research and design are often taught separately from each other, while in professional STEM practices, many projects are neither 'research only' or 'design only'-they are both. In this study, we aimed to provide insights in teachers' personal and shared knowledge on how research and design can be connected. To this end, we examined the development of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 52 publications
1
24
0
4
Order By: Relevance
“…Magnusson, Krajcik, & Borko, 1999). In other studies into teachers' ideas in design-education contexts, using these four pedagogical elements indeed provided insight in teachers' pedagogical ideas (Rahimi, Barendsen, & Henze, 2016;Vossen, Henze, De Vries, & Van Driel, 2019).…”
Section: Teacher Pedagogical Ideasmentioning
confidence: 88%
“…Magnusson, Krajcik, & Borko, 1999). In other studies into teachers' ideas in design-education contexts, using these four pedagogical elements indeed provided insight in teachers' pedagogical ideas (Rahimi, Barendsen, & Henze, 2016;Vossen, Henze, De Vries, & Van Driel, 2019).…”
Section: Teacher Pedagogical Ideasmentioning
confidence: 88%
“…"Several authors increasingly see professional teacher development as a process comprised not only of initial training and continuing education, but also of peer input and personal reflexivity in other personal or professional situations" (Daele and Charlier, 2006, p. 90). In the face of such challenges, practice-based communities (Chanier and Cartier, 2006;Lave and Wenger, 1991), professional learning communities Although such complex methods (Vossen et al, 2019) can be widely found in different forms, some authors have nonetheless attempted to define their invariable attributes. Thus, for example, according to Bielaczyc and Collins (1999), eight dimensions must be present to create a productive learning community: a common and shared goal; meaningful activities; an instructor who acts as a guide/group leader; participants who are seen as resources; who are occasionally put at the centre of the activity; a message that is geared toward co-building; a shared subject of knowledge; and artifacts that are created collaboratively.…”
Section: The Learning Community As Training Methodsmentioning
confidence: 99%
“…Retrieving information from other fields related to the area in which the design problem is positioned Examine which research or design methods to apply FUN_DforR Design can enhance a research project when there is a 'need to do': for example, by designing an experimental setup. (Kolodner et al 2003;Vossen et al 2019).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…As students do not always conduct research activities during a design project themselves, it is the role of the teacher to guide students through the design process and ensure the design decisions made are of sufficient quality, which can be enhanced by research activities. However, teachers of STEM subjects are usually not experienced designers themselves (Banilower et al 2013;Vossen et al 2019). Teaching design can pose problems for teachers, and this can lead to design not being used to maximum pedagogical advantage in the classroom (Burghardt and Hacker 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation